Physics Learning with the Problem Based Learning (PBL) Model Based on Electronic Liveworksheets to Improve Critical Thinking Skills - Dewi, Sri; Nisa’, Khoirun (Universitas Negeri Surabaya, 2025)
Objective: This study aims to determine the effectiveness of the Problem-Based Learning (PBL) model based on electronic liveworksheets in improving students' critical thinking skills. Method: This research employed a quantitative quasi-experimental design with a pre-test and post-test control group. The study subjects were 64 eleventh-grade students from SMA Negeri 1 Bluluk, divided into an experimental class (PBL with electronic liveworksheets) and a control class (conventional PBL), each consisting of 32 students. Research instruments included learning implementation observation sheets, critical thinking skills test questions, and student response questionnaires. Data were analyzed using prerequisite tests (normality and homogeneity) and hypothesis tests (paired t-test, N-Gain, and Effect Size). Results: The results showed that the learning implementation reached a